Distinct phenotypes in the preeclamptic-like mouse model induced by adenovirus carrying sFlt1 and recombinant sFlt1 protein - Yingying Wei; Haojun Tian; Xuancheng Wei; Ai Zhang; Mengtian Wei; Ruixue Wang; Lu Zhang; Ping Qiao; Kai Wang (European Journal of Medical Research)
Abstract Background Preeclampsia (PE) is a pregnancy-specific, multisystemic disorder that affects 2–8% pregnancies worldwide and is a leading cause of maternal and perinatal mortality. At present, there is no cure for PE apart from delivery the placenta. Therefore, it is important and urgent to possess a suitable animal model to study the pathology and treatment of PE. When exogenous soluble fms-like tyrosine kinase-1 (sFlt-1) is administered, pregnant animals develop a PE-like phenotype. However, there is no report on the comparison between different methods of constructing PE mouse models using sFlt-1. Methods In this study, the adenovirus carrying sFlt-1(ADV-Flt-1) and recombinant murine sFlt-1 protein (RM Flt-1) are two different methods were used to induce and compare PE-like mouse models. Pregnancy outcomes were examined on E14.5 and E17.5. Results Our data showed that on E14.5, the adenovirus carrying sFlt-1 induced PE-like phenotype, whereas recombinant murine sFlt-1 protein not. On E17.5, both the two methods induced PE-like phenotype including hypertension, proteinuria, fetal growth restriction, placental and glomerular endotheliosis. Importantly, in the adenoviral-mediated sFlt-1 group, the circulating concentration of sFlt-1 were higher than in the recombinant sFlt-1 group, leading to earlier and more severe symptoms of PE. The ADV-Flt-1 group is easy to operate, quickly effective and efficient. The RM Flt-1 group is safer and more stable, with good repeatability, but slower to take effect. Conclusions We proposed that the adenoviral-mediated sFlt-1 model can better simulate early-onset and severe PE.